A Friend of Kissinger : A Novel - Milofsky, David (Book collections on Project MUSE., 2003)
Danny's bubble-like existence in paradisal Madison is broken when his father, a concert pianist and professor, is stricken with illness and must give up his professorship. The family moves to Milwaukee to live at the brink of poverty while his father gets sicker, his artistic mother struggles as bread-winner, and his brother becomes delusional. Here, Danny finds himself in the uncertain position of having to accept the responsibilities of manhood while still struggling with adolescence. In a world that keeps shifting, Danny befriends the son of a gangster and, through his brushes with that compelling world of crime, finds his way to a new confidence.